Multidecadal Water Mass Dynamics on the West Greenland Shelf. Issue 7 (28th June 2022) - Mortensen, J.; Rysgaard, S.; Winding, M. H. S.; Juul‐Pedersen, T.; Arendt, K. E.; Lund, H.; Stuart‐Lee, A. E.; Meire, L.
Abstract: The waters on the West Greenland continental shelf and slope play an important role in the global climate system with their link to the subpolar North Atlantic Ocean circulation system and the Greenland Ice Sheet. Lately, low temperature waters on the West Greenland shelf have been observed as far south as ∼64°N and associated with a cold and relatively saline water mass originating north of Davis Strait in Baffin Bay referred to as Baffin Bay Polar Water (BBPW). Here we use long, seasonal hydrographic time series from West Greenland at ∼64°N to study how frequently BBPW is reaching this far south. The analysis covers the period 1950–2018 with a data gap between 1988 and 2005. BBPW was observed frequently and was responsible for the temperature changes observed in the late 1960s–1980s and more intermittently post‐2008. Some of the large temperature changes we observe in the time series have previously been ascribed to "Great Salinity Anomalies" (GSAs) propagating around the subpolar North Atlantic Ocean circulation system. The prevailing view of the propagation of GSAs has been ascribed to advection of anomalies along the large‐scale circulation system. Our study shows that BBPW may play an important role in the interpretation of GSAs and melt of the Greenland Ice Sheet. Large temporal temperature changes at ∼64°N are associated with arrival of BBPW from the north and not advection of anomalies with the large‐scale current system from the south. This advocates for a shift in water masses caused by changes in the position and/or strength of oceanic currents. Plain Language Summary: The Greenland Ice Sheet is likely to experience significant mass losses in coming decades. One of the challenges is to understand the changing physical nature of waters on the adjacent continental shelf and their effects on tidewater glacier fjords. Lately, low temperature waters on the West Greenland shelf have been observed as far south as ∼64°N and associated with a cold and relatively saline water known as Baffin Bay Polar Water (BBPW) mass originating north of Davis Strait in Baffin Bay. We use unique, long, seasonal hydrographic time series from the West Greenland continental shelf at ∼64°N and an adjacent proglacial fjord to study how frequently BBPW is reaching this far south in the period 1953–2018. BBPW was observed at ∼64°N in the following years: 1954–1955, 1968–1976, 1980–1983, 1985, 1987, 2008, 2012, and 2015–2017. This study shows that BBPW may play an important role in the interpretation of the large‐scale subpolar North Atlantic Ocean circulation system and melt of the Greenland Ice Sheet. Key Points: We present long‐term seasonal hydrographic time series from the West Greenland shelf at 64°N and adjacent proglacial fjord The time series reveal the recurrence of Baffin Bay Polar Water (BBPW), a northern water mass originating in Baffin Bay Large temporal temperature changes are associated with arrival of BBPW and not advection of anomalies with the large‐scale current system